Identification of Gamma-Aminobutyricacid (GABA) of Tempeh Made from Koro Kratok (Phaseolus lunatus) Bean and Beluntas (Plunchea indica) Leaves as Glucose Stabilizer - Istiqomah Istiqomah; Dina Mustika Rini; Larisa Tania; Sholihatil Hidayati; Mohammad Rofik Usman (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The tempeh available on the market is predominantly made from imported soybeans, but alternative formulations using locally sourced legumes, such as koro kratok (Phaseolus lunatus), have been explored. This study investigates the potential of koro kratok tempeh enriched with Plunchea indica (beluntas) leaves to improve its functionality. The study will evaluate gamma-aminobutyric acid (GABA) levels and physicochemical changes during fermentation. Tempeh was produced using different koro kratok-to-P. indica leaf ratios (100:0, 75:25, and 50:50). Key parameters observed included mycelium development and the content of fat, moisture, ash, protein, carbohydrates, and pH. Adding P. indica increased the fat content by 0.66–2.28%, the moisture content by 68.81–78.42%, and the ash content by 0.36–1.09%. Meanwhile, the protein content ranged from 6.62–8.87%, the carbohydrate content from 12.07–21.31%, and the pH between 4.21–4.25. The inclusion of P. indica also altered the profile of dominant volatile compounds. GABA was detected in all samples, and in vivo studies showed improved blood glucose levels and glucose tolerance in prediabetic rats. These results suggest that koro kratok tempeh enriched with P. indica leaves could be a promising functional food for regulating blood glucose.